Histological and Biochemical Effects of Cadmium chloride on Kidney and Heart Tissues and Curative Roles of Brassica nigra Seeds Extract in Male Rats (Eurasian Medical Research Periodical, 2022)
Cadmium (Cd) is known as an inorganic highly toxicant and widely distributed in the environment and causes various disease conditions, and it is widely used in numerous industrial processes and it is a component of many commercial products. The major pharmacological producers are currently running excessive research on plants to introduced new drugs in the medical treatments. Brassica nigra has antioxidant, antiinflammatory, antiepileptic, antidiabetic and many other pharmacological properties.